Annotated bibliography Maguindanaon, Tausug, Yakan studies - Bakuludan, Samier M. (University of the Philippines, Center for Integrative and Development Studies, Mindanao Studies Program, 1996)
This is an ethnic bibliography of published and unpublished materials on Maguindanao, Tausug, and Yakan studies. This work aims to contribute to a meaningful approach to Mindanao's history and culture. The entries are arranged alphabetically by author. It is divided into three parts and each annotator represent their own people: Bakuludan is a Maguindanaon, Hairulla is from Sulu, and Mariano is a Yakan.